DYNAMIC VOLTAGE RESTORER DEVELOPMENT AND TESTING - Monteiro, T. C.; Camargo, J.; Ahn, S. U.; Bormio, E.; Terrazas, T. M. [UNESP]; Marafao, F. P. [UNESP]; Giaretta, A. R.; Jardini, J. A.; Matakas, L.; Komatsu, W.; IEEE (Ieee, 2011)
The growing use of sensitive loads in the electric power system, especially in industrial applications, increases voltage sags related production losses considerably, stimulating a demand for power electronics' based solutions to mitigate the effects of such problems. This paper shows the implementation and some industrial certification tests of a power equipment prototype designed to correct sags and swells, a dynamic voltage restorer, which is one of the many possible solutions for voltage sags and swells problems.. Experimental results of a 75kVA prototype are shown both in laboratory and full load conditions, in a certification institution (IEE-USP).
Keywords: PWM Converter; Power Quality; Dynamic Voltage Restorer; Voltage Sags; Voltage Swells